Pengaruh Lokasi Dan Harga Terhadap Keputusan Pembelian Perumahan Puri Hijau Di Kabupaten Cirebon - Nabila Christina Ayu Aprilia; Gytha Nurhana Dhea Praadha Gitama (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2022)
This study aims to determine whether there is an influence of location on purchasing decisions for Puri Hijau Housing in Cirebon district, the effect of price on purchasing decisions for Puri Hijau Housing in Cirebon district, the influence of location and price simultaneously on purchasing decisions for housing Puri Hijau Cirebon housing. The population studied in this study were 125 consumers of Puri Hijau Housing. The sampling technique used the slovin formula with a total sample of 56 consumers. The data collection technique uses a Google Form questionnaire that has been tested for validity and reliability tests. The data analysis technique used is multiple linear regression analysis. The results showed that: there is an influence of location on the decision of Puri Hijau Housing in Cirebon district, there is an influence of price on the purchasing decision of Puri Hijau Housing in Cirebon district, there is a simultaneous influence of location and price on the purchasing decision of Puri Hijau Housing in Cirebon district Key words: Location, Price and Purchase Decision